PENINGKATAN KOMPETENSI SUMBER DAYA MANUSIA MELALUI KEMAMPUAN INTELEKTUAL, PEMBELAJARAN INDIVIDUAL DAN KEMAMPUAN PENYERAPAN PENGETAHUAN - Slamet Suyono (Jurnal Riset Bisnis Indonesia, 2015)
This study is to describe and analyze the improvement of the competence of human resourcesthrough intellectual ability, individual learning and knowledge absorption capability. The purposeof this study to examine and analyze 1) the effect of intellectual ability to the competence 2)the influence of individual learning on the competence, 3) the effect of intellectual ability to theabsorption of knowledge 4) the effect of individual learning to the knowledge absorption capacity 5)the effect of absorption of knowledge to the competence. This study was conducted to Employeesin the Department of Revenue, Finance and Asset Management District Semarang. The methodof data collection in this study through a list of questions / questionnaire with 80 respondents forsample. Based on SEM analysis the results showed that if the intellectual capability increases, thecompetence of human resources is increasing, if the individual learning increases, the competenceof human resources is increasing, if the intellectual capability increases, the absorption of knowledgeis increasing, if individual learning increases, the absorption knowledge is increasing, and if theknowledge absorption capacity increases, the competence of human resources is increasing. Themanagerial implications of this study are as follows; associated with increasing intellectual ability,individual learning, knowledge absorption capability and competence of the employees in RevenueService Financial and Asset Management should be given awards (reward), those are by improvingeducation, training, education and training, technical assistance, mutation in order to increaseknowledge transfer even promotion position or promotion to positions.Keywords :intellectual ability, individual learning, knowledge absorption and capability competence